ECONOMIC SECURITY IN THE FORMATION AND DEVELOPMENT OF PRODUCTION INDUSTRY CLUSTERS (Marketing Journal, 2025)
The article explores the issues of ensuring economic security in the process of forming and developing industrial clusters. The relevance of the cluster approach as a tool for enhancing the competitiveness and resilience of the economy is substantiated. The concept of "economic security" is clarified in the context of cluster formations, and the main threats and risks that may affect the efficiency of cluster functioning are identified. Directions for improving mechanisms of economic security at different stages of cluster development are pr oposed. The results obtained can be used in the development of regional development programs and cluster policies. 286
Keywords: cluster; industry; economic security; risks; sustainable development; regional economy; competitiveness